Development of a rapid and accurate UHPLC-PDA-FL method for the quantification of phenolic compounds in grapes. (1st January 2021) - V. González de Peredo, Ana; Vázquez-Espinosa, Mercedes; Piñeiro, Zulema; Espada-Bellido, Estrella; Ferreiro-González, Marta; F. Barbero, Gerardo; Palma, Miguel
Highlights: A new UHPLC-PDA-FL method for the quantification of phenolic compounds in grapes. Mobile phase, gradient, column temperature and flow rate were optimized. Excellent detection and quantification limits, precision and selectivity were obtained. Several varieties of grapes were studied to evaluate the applicability of the method. Abstract: Grapes are a great source of phenolic compounds, which have excellent antioxidant properties. Efficient analytical methods are necessary to selectively and precisely determine these compounds content in grapes. In this study, a reverse-phase ultra-high performance liquid chromatography (UHPLC) method with fluorescence and photodiode array detection has been developed to determine and quantify 27 of the main phenolic compounds present in grapes. An ACQUITY UPLC® BEH C18 (50 mm × 2.1 mm i.d., 1.7 mm particle size) column was employed. A gradient method was developed and column temperature (25–55 °C), as well as flow rate (0.6–0.75 mL min −1 ), were optimized. The optimum conditions allowed the separation of all the compounds in less than 9 min. The method was validated and demonstrated excellent detection and quantification limits, precision, and selectivity. Finally, several grape varieties were studied in order to demonstrate the applicability of the method to the analysis of real matrix samples.